Selective solvent-induced reconstruction in confined space: one-dimensional mesoporous block copolymer structures in cylindrical nanopores. Issue 22 (23rd May 2017) - Chang, Chun-Wei; Chi, Mu-Huan; Ko, Hao-Wen; Chu, Chien-Wei; Fang, Zhi-Xuan; Tu, Yi-Hsuan; Chen, Jiun-Tai
Abstract : The formation of polymer nanostructures confined in cylindrical nanopores via a novel selective solvent-induced reconstruction process is investigated. Abstract : We investigate the formation of polystyrene- block -poly(methyl methacrylate) (PS- b -PMMA) nanostructures confined in cylindrical nanopores via a novel selective solvent-induced reconstruction process. The key factors of the morphologies of the nanostructures are determined, including the choice of solvents, the molecular weights of the polymers, and the pore diameters of the templates.